Digital financial innovation and MSMES’ sustainable performance in developing countries: A prisma-based systematic review - Eka Yuliyanti; Anis Turmudhi; Tri Sumiyanti; Azis Nur Rosyid; Zati Rizka Fadhila (Journal of Economics Research and Policy Studies, 2026)
MSMEs play a vital role in economic growth and job creation in developing countries, yet they still face numerous challenges that can be addressed through digital financial innovation, although evidence on their impact on sustainable performance remains fragmented and not yet comprehensively integrated. This study presents a PRISMA-based systematic literature review of 40 studies retrieved from Web of Science and Scopus (2020–2025). The selected studies were synthesized using thematic content analysis to identify dominant theoretical foundations, methodological approaches, and contextual factors. The findings show that digital financial innovation improves MSME performance through enhanced financial inclusion, operational efficiency, and business resilience. However, the magnitude of these effects varies across countries due to differences in digital infrastructure, regulatory environments, and digital literacy levels. Cross-sectional designs dominate the literature, while longitudinal evidence remains limited. Overall, institutional and infrastructural readiness is a key determinant of the effectiveness of digital financial innovation in supporting MSME sustainability.